2019
DOI: 10.3390/molecules24081463
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of the Tetrapeptide Ac-His-Arg-(pI)DPhe-Tic-NH2 at the Mouse Melanocortin Receptors: Modification at the (pI)DPhe Position Leads to mMC3R Versus mMC4R Selective Ligands

Abstract: The five melanocortin receptors (MC1R–MC5R) are involved in numerous biological pathways, including steroidogenesis, pigmentation, and food intake. In particular, MC3R and MC4R knockout mice suggest that the MC3R and MC4R regulate energy homeostasis in a non-redundant manner. While MC4R-selective agonists have been utilized as appetite modulating agents, the lack of MC3R-selective agonists has impeded progress in modulating this receptor in vivo. In this study, the (pI)DPhe position of the tetrapeptide Ac-His-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
(86 reference statements)
2
7
0
Order By: Relevance
“…These values are similar to a prior report where this sequence had agonist EC 50 values of 0.6, 14, and 7.6 nM at the MC1R, MC3R, and MC5R, respectively, and a pA 2 value of 5.9 at the MC4R. 18 Inverting the stereochemistry at the fourth position to DTic (yielding tetrapeptide 2) resulted in equipotent activities at the MCRs compared to 1. When reporting similar tetrapeptides, Fleming et al also observed comparable activities when Tic or DTic was substituted at the fourth position.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…These values are similar to a prior report where this sequence had agonist EC 50 values of 0.6, 14, and 7.6 nM at the MC1R, MC3R, and MC5R, respectively, and a pA 2 value of 5.9 at the MC4R. 18 Inverting the stereochemistry at the fourth position to DTic (yielding tetrapeptide 2) resulted in equipotent activities at the MCRs compared to 1. When reporting similar tetrapeptides, Fleming et al also observed comparable activities when Tic or DTic was substituted at the fourth position.…”
supporting
confidence: 89%
“…The parent tetrapeptide in this study, 1 (Ac-His-Arg-DBip-Tic-NH 2 ), possessed full agonist efficacy at the MC1R, MC3R, and MC5R (0.5, 22, and 9 nM potencies, respectively; Tables and ), partially stimulated the MC4R at 100 μM concentrations (35% the maximal signal of NDP-MSH), and possessed submicromolar antagonist potency at the MC4R (pA 2 = 6.5). These values are similar to a prior report where this sequence had agonist EC 50 values of 0.6, 14, and 7.6 nM at the MC1R, MC3R, and MC5R, respectively, and a pA 2 value of 5.9 at the MC4R . Inverting the stereochemistry at the fourth position to DTic (yielding tetrapeptide 2 ) resulted in equipotent activities at the MCRs compared to 1 .…”
supporting
confidence: 89%
See 3 more Smart Citations